(untitled) - Halliday, David (New York, 1997)
Volume 2 of the fifth edition of this introduction to physics. This text addresses the issue of building "bridges of reason", so that students may move from qualitative understanding of any given physics concept to making decisions about how to solve a problem involving that concept.
Keywords: Physics,Vật lý; Handbooks, manuals, etc.,Cẩm nang, sách hướng dẫn